ANALISIS: PENGARUH PENANAMAN MODAL LUAR NEGERI (PMDN) DAN PENANAMAN MODAL ASING (PMA) TERHADAP PRODUK DO ESTIK REGIONAL BRUTO (PDRB) DI PROVINSI JAMBI - Hanani Aprilia Adi; Syahlina Syahlina (FEB Universitas Sultan Ageng Tirtayasa, 2020)
The purpose of this research is to analyze the influence of domestic investment (DI) and foreign direct investment (FDI) on Gross Domestic Regional Product (GDRP) in Jambi province in the period 2000 to 2018.This research uses multiple linear regression analysis models with time series data. The results show that the variable domestic investment and foreign direct investment had a significant and positive effect on the gross regional domestic product.